Hubungan Sekolah dengan Masyarakat di Sd Negeri No. 195/Vi Pematang Kancil - Dandi Kurniawan; Vina Sulistia; Yantoro Yantoro; Bradley Setiyadi (Advances In Social Humanities Research, 2023)
The objective of this study was to describe the relationship between the school and community planning, to determine the implementation of school and community relations , to know the principals evaluate the implementation of school and community relations.  This research is a qualitative descriptive study. The subject of this research is principal, teachers, students, and parents committee chairman. Data collection techniques are observation, interviews , and documentation. Data analysis techniques is data collection, data reduction, data presentation, and conclusion. After the study concluded that the relationship of the school with the community goes well.